Significance of residual stresses in fatigue life prediction of micro gas turbine blades. (February 2021) - Ramakokovhu, Unarine; Desai, Dawood; Snedden, Glen; Jamiru, Tamba
Highlights: Continuous development in fatigue life prediction and analyses methods. Multi-axial fatigue life prediction with residual stresses considered. Experimental and simulation methods followed by a probabilistic approach. Stress relaxation of an aircraft turbine blade subjected to operating conditions. Significant deviations in fatigue life as residual stresses are being relaxed. Abstract: The aim of this study is to investigate the significance of residual stresses in fatigue analyses of micro gas turbine blades in order to attain accurate fatigue life estimates; such studies have not been adequately investigated. This was achieved by manufacturing test samples using Additive Manufacturing (AM). The samples were subsequently heat-treated in order to mimic the operating conditions of the engine and then evaluated experimentally for the presence of residual stresses. In order to incorporate these residual stresses into engine operating conditions, an ABAQUS Finite Element Analysis (FEA) was conducted to define stresses which are effective during operation. Subsequently, a fatigue software (Fe-safe) was used to determine the fatigue behavior of the bladed disk while taking into consideration the in-plane residual stresses. The results acquired from this study showed an average residual stress contribution of 70% towards the fatigue life estimated cycles to failure of engines undertaking short flight missions. As the flight time increases, the residual stress influence decreases due to stress relaxation. This study, therefore, concluded that the inclusion of in-plane residual stresses in fatigue life estimates is significant for turbine blades operating at short flight time intervals with less effect on long mission operations.